PENERAPAN PEMBELAJARAN KOOPERATIF PADA MATERI RANGKAIAN LISTRIK TERHADAP HASIL BELAJAR SISWA DI MTS MATLAâ€™UL-ANWAR - Almuharramah, Dhiya; Sitompul, Stepanus Sahala; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe study aimed to determine the effect of applying the cooperative learning model of think pair share type on electrical circuits in improving student learning outcomes at MTs Mathla'ul Anwar Pontianak. This research was in the form of classroom action research with the sample taken using the intact group technique consisting of 29 students of class IX A. The data collection tool was a validated test of the question (the validity level of cycle I is 3.8 and cycle II is 3.9 in the medium category) and tested for reliability (treasonability 0.75 for the first cycle and 0.60 in the second cycle so that it was in the high category). Based on data analysis, it was obtained the level of class completeness in the first cycle of 86.20% and 79.31% in the second cycle. Besides the level of learning implementation 78.3% in the first cycle of the first meeting, 75.0% in the second cycle of the second meeting and 100% in the second cycle. Thus the cooperative learning model of the think pair shared can improve student learning outcomes about electrical circuits at MTs Mathla'ul Anwar Pontianak.Â Keywords: Electrical Circuit, Learning Outcomes, Think Pair Share.